2013
DOI: 10.1534/genetics.113.156562
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mob2, a Novel Regulator of Larval Neuromuscular Junction Morphology, in Natural Populations of Drosophila melanogaster

Abstract: Although evolutionary changes must take place in neural connectivity and synaptic architecture as nervous systems become more complex, we lack understanding of the general principles and specific mechanisms by which these changes occur. Previously, we found that morphology of the larval neuromuscular junction (NMJ) varies extensively among different species of Drosophila but is relatively conserved within a species. To identify specific genes as candidates that might underlie phenotypic differences in NMJ morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Additional genetic evidence that fly Mob2 is required for Tricornered activation comes from studies of the larval neuromuscular junctions, where synaptic contacts form between motor neuron axons and muscle. Campbell and Ganetzky (2013) showed that mob2 is required for normal development of neuromuscular junctions. Each junction involves multiple neuronal contacts called synaptic boutons.…”
Section: Fly Tricornered Kinases Acts In a Hippo-like Pathway Controlmentioning
confidence: 99%
“…Additional genetic evidence that fly Mob2 is required for Tricornered activation comes from studies of the larval neuromuscular junctions, where synaptic contacts form between motor neuron axons and muscle. Campbell and Ganetzky (2013) showed that mob2 is required for normal development of neuromuscular junctions. Each junction involves multiple neuronal contacts called synaptic boutons.…”
Section: Fly Tricornered Kinases Acts In a Hippo-like Pathway Controlmentioning
confidence: 99%
“…This and other mapping resources for model organism communities [55, 54, 28, 56, 48, 49, 57] not only enable mapping of phenotypic differences in parental lines, but can unmask cryptic variation that provides a powerful complement to laboratory mutagenesis (e.g. [58, 59]).…”
Section: Capturing Natural Functional Variation In Model Organismsmentioning
confidence: 99%
“…Homozygous trc 1 mutants, a previously characterized loss-of-function point mutant allele[ 29 ], do not typically survive beyond the late second or early third-instar stage[ 22 ] and are also much smaller compared to age-matched wild-type (WT) larvae. This is likely because Trc regulates multiple processes that are important for survival[ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous data indicated that Tsc2 acts presynaptically to regulate synapse growth[ 10 ]. In addition, Mob2, an interactor of Trc 1 , can regulate synapse growth presynaptically[ 22 ]. These data suggest that the presynaptic pool of Trc may be required to regulate synapse number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation